Directions for a Change in Tour Operators Market Regulation (in Poland and the European Union) - Panasiuk , Aleksander (Studia Oeconomica Posnaniensia, 2018)
The study involved the regulation of the tour operators market. The issue was presented with the example of the principles of the functioning of the Polish tour operators market. The background to these considerations are the rules of the functioning of this market in the European Union. Tour operator’s market regulation in the EU is undergoing a major transformation. EU Member States are implementing new regulations under the new EU directive on the tour operators market into tourism law. The aim of the study is to present changes in the regulation of the tour operators market together with an attempt to assess the consequences of these changes for the model of the functioning of this market. The following sections discuss: the concept and scope of the tour operator market, the scope of the regulation of the analyzed market in Poland and the trends of changes in the regulation of the tour operators market as a result of the changes introduced by the new EU directive.